Optical measurement of the ambipolar diffusion length in a ZnCdSe-ZnSe single quantum well - DONEGAN, JOHN FRANCIS; MC CABE, EITHNE MARY; HEGARTY, JOHN (American Institute of Physics, 1997)
We describe a straightforward technique for the measurement of carrier diffusion in semiconductors. Using an optical microscope we can spatially image luminescence with a resolution of ~ 500 nm. We measured the ambipolar diffusion length in a Zn0.75Cd0.25Se?ZnSe single quantum well by fitting the spatially resolved luminescence profile with the solution of the two-dimensional diffusion equation. The ambipolar diffusion length was found to be 498 nm at a carrier density of ~ 1 ? 1018 cm ? 3 and we deduce an ambipolar diffusion constant of 1.7 cm2 s ? 1.
PUBLISHED
Keywords: zinc compounds; cadmium compounds; II-VI semiconductors; semiconductor quantum wells